1999
DOI: 10.1152/ajpgi.1999.277.5.g1017
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol inhibits spontaneous action potentials and calcium currents in guinea pig gallbladder smooth muscle

Abstract: Elevated cholesterol decreases agonist-induced contractility and enhances stone formation in the gallbladder. The current study was conducted to determine if and how the electrical properties and ionic conductances of gallbladder smooth muscle are altered by elevated cholesterol. Cholesterol was delivered as a complex with cyclodextrin, and effects were evaluated with intracellular recordings from intact gallbladder and whole cell patch-clamp recordings from isolated cells. Cholesterol significantly attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 35 publications
(53 reference statements)
5
55
0
Order By: Relevance
“…Initially described in hepatocytes [32], the mere presence of these organelles in the cholecystocytes islikelyindicative of excessive sterols and cholesterol intake either due to a high level of circulating lipids and=or the inflammatory processes. This exaggerated intake could alter the homeostatic functions of their membranes because an excessive intake in the smooth muscles of the gallbladder wall alters their membrane potentials [33]. In chronic cholecystitis, the epithelial intake of cholesterol and many other lipids have been demonstrated [3,4,11,16].…”
Section: Membrane Alterations Lipids and Liposomesmentioning
confidence: 99%
“…Initially described in hepatocytes [32], the mere presence of these organelles in the cholecystocytes islikelyindicative of excessive sterols and cholesterol intake either due to a high level of circulating lipids and=or the inflammatory processes. This exaggerated intake could alter the homeostatic functions of their membranes because an excessive intake in the smooth muscles of the gallbladder wall alters their membrane potentials [33]. In chronic cholecystitis, the epithelial intake of cholesterol and many other lipids have been demonstrated [3,4,11,16].…”
Section: Membrane Alterations Lipids and Liposomesmentioning
confidence: 99%
“…MβCD depletes selectively cholesterol from the plasma membrane (Kilsdonk et al, 1995;Christian et al, 1997;Ilangumarn and Hoessli, 1998) and cholesterol-CDs complexes have been shown to increase the cellular content of cholesterol (Bernard et al, 1990;Christian et al, 1997;Racchi et al, 1997;Jennings et al, 1999). Depletion of plasma membrane cholesterol with MβCD is usually accomplished by incubations for short (∼1 h) periods with high (∼1-2%) concentrations of MβCD (Ilangumaran and Hoessli, 1998;Abrami et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol availability has been reported to modulate the activity of several different ion channels (Bolotina et al, 1989;Jennings et al, 1999;Martens et al, 2001;Lockwich et al, 2000), in addition to that of VSOAC. In agreement with previous studies of non-neural cells, depletion of cholesterol from SH-SY5Y cells by pretreatment with CD under relatively mild conditions (5 mM for 10 min) facilitated the basal release of taurine in response to hypotonicity.…”
Section: Discussionmentioning
confidence: 99%